(3QSGdI aj KHhJ GdbUGU hGSJjaGA GdMbhb jhe GdLRGAs - (3GHf MeRI, eMeO Hf MeRI, cGf MjG (B1113 (3g`s ((3eMeO Hf GdMGL Ydj CafOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hSdGe Ydi YHGOg GdPjf GUWai CYde Cfg GJab GdYdeGA Ydi KHhJ GdbUGU hGSJjaGA GdMbhb jhe GdLRGA MJi MOhg ef GdYbGFO GdESdGejIs
(3BNQgG (B:s
(3aj GdBNQI aJNQL Yf GdEjeGf hfONd aj NHQ cGf aEfg QO ddfUhU hNQb dELeGY GdeSdejf hEfcGQ deG gh ef VQhQGJ GdOjfs
(3fSNI efbhdI Yf fSNI GdeDda eDQNI H SfI (B1103 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3 / 268s
(3agQS GdNOjhjI (B7 / 1 402s
(3agQS eNWhWGJ GdXGgQjIs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs